2016
DOI: 10.1002/path.4734
|View full text |Cite
|
Sign up to set email alerts
|

Glioma progression is mediated by an addiction to aberrant IGFBP2 expression and can be blocked using anti-IGFBP2 strategies

Abstract: Insulin-like growth factor binding protein 2 (IGFBP2) overexpression is common in high-grade glioma and is both a strong biomarker of aggressive behaviour and a well-documented prognostic factor. IGFBP2 is a member of the secreted IGFBP family that functions by interacting with circulating IGFs to modulate IGF-mediated signalling. This traditional view of IGFBP2 activities has been challenged by the recognition of the diverse functions and cellular locations of members of the IGFBP family. IGFBP2 has been prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 30 publications
4
34
0
Order By: Relevance
“…Examination of the female-specific transcripts revealed the Integrin signaling pathway as the most significant pathway that distinguished fc3 from other female clusters ( Figure 5C). Six of the nine transcripts from this pathway (PLAT (29), CHL1 (30,31), FERMT1 (32), PCDH8 (33), IGFBP2 (34,35), POSTN (36)) have previously reported roles in glioma, and three (PLAT, IGFBP2 and POSTN) have been reported to distinguish Proneural from Classical subtype GBM consistent with the high rate of IDH1 mutant tumors in this cluster. Six of the nine genes (AK5, AMIGO2, PLAT, CHL1, PCDH8, IGFBP2) were downregulated in fc3 compared to other female clusters suggesting that better survival in fc3 patients is favored by tumors with reduced integrin signaling (data not shown).…”
Section: Pathway Analysissupporting
confidence: 53%
“…Examination of the female-specific transcripts revealed the Integrin signaling pathway as the most significant pathway that distinguished fc3 from other female clusters ( Figure 5C). Six of the nine transcripts from this pathway (PLAT (29), CHL1 (30,31), FERMT1 (32), PCDH8 (33), IGFBP2 (34,35), POSTN (36)) have previously reported roles in glioma, and three (PLAT, IGFBP2 and POSTN) have been reported to distinguish Proneural from Classical subtype GBM consistent with the high rate of IDH1 mutant tumors in this cluster. Six of the nine genes (AK5, AMIGO2, PLAT, CHL1, PCDH8, IGFBP2) were downregulated in fc3 compared to other female clusters suggesting that better survival in fc3 patients is favored by tumors with reduced integrin signaling (data not shown).…”
Section: Pathway Analysissupporting
confidence: 53%
“…[7][8][9] IGFBP2 is a member of the secreted IGFBP family that functions by interacting with circulating IGFs to modulate IGF-mediated signaling. 10 As a secreted protein, IGFBP2 was reported to be a human tumor antigen that elicited T-cell and B-cell immunity in patients with some cancers. 11 The circulating IGFBP2 antibodies may provide a potential approach for diagnosing early cancers in a broad population of patients.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we have studied the eff ect of titanium nitride and chromium disilicide nanoparticles on the expression of a subset of genes encoding different regulatory factors (IGFBP1, IGFBP2, IGFBP3, IGFBP4, IGFBP5, CD36, and PECAM1) and enzyme SNARK/NUAK2, which play an important role in various metabolic pathways and thus control the cell proliferation and apoptosis as well as angiogenesis and metastasis (Praveen Kumar et al 2014;Baxter 2015;Kim and Lee 2015;Musumeci et al 2015;Ding et al 2016;Kim et al 2016;Miller et al 2016;Phillips et al 2016;Guaita-Esteruelas et al 2017;Pascual et al 2017). For titanium dioxide nanoparticles, which are widely used in the number of applications, including cosmetic creams, toothpastes, and component of surgical implants, it has been shown that long-term exposure to these nanoparticles led to accumulation of these nanoparticles in brain, over-proliferation of glial cells and signifi cant changes in brain gene expressions as well as to neurogenic disease states in mice (Ze et al 2014;Rollerova et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IGFBP2 enhances VEGF gene promoter activity and consequent promotion of angiogenesis by neuroblastoma cells . Recently, Phillips et al (2016) revealed that IGFBP2 not only is a driver of glioma progression and a prognostic factor but also is also required for tumor maintenance and can be blocked using anti-IGFBP2 strategies. Furthermore, cell viability during glucose deprivation is enhances by TRIB3 (pseudokinase Tribbles homolog 3) through upregulation of IGFBP2, which is recognized as a novel nutrient defi ciency survival factor (Ord et al 2015).…”
mentioning
confidence: 99%